Assessment of the Human Factors Analysis and Classification System (HFACS): Intra-rater and inter-rater reliability. (February 2016) - Ergai, Awatef; Cohen, Tara; Sharp, Julia; Wiegmann, Doug; Gramopadhye, Anand; Shappell, Scott
Highlights: HFACS is a reliable method for coding accident/incident causal factors. HFACS has been shown to possess both inter- and intra-rater reliability. Training, number of causal factors assessed, and adherence to the HFACS framework impact reliability. Abstract: The Human Factors Analysis and Classification System (HFACS) is a framework for classifying and analyzing human factors associated with accidents and incidents. The purpose of the present study was to examine the inter- and intra-rater reliability of the HFACS data classification process. Methods: A total 125 safety professionals from a variety of industries were recruited from a series of two-day HFACS training workshops. Participants classified 95 real-world causal factors (five causal factors for each of the 19 HFACS categories) extracted from a variety of industrial accidents. Inter-rater reliability of the HFACS coding process was evaluated by comparing performance across participants immediately following training and intra-rater reliability was evaluated by having the same participants repeat the coding process following a two-week delay. Results: Krippendorff's Alpha was used to evaluate the reliability of the coding process across the various HFACS levels and categories. Results revealed the HFACS taxonomy to be reliable in terms of inter- and intra-rater reliability, with the latter producing slightly higher Alpha values. Conclusion: Results support the inter- and intra-rater reliability of the HFACS framework but also reveal additional opportunities for improving HFACS training and implementation.